POLITIK IDENTITAS SEBAGAI MANIFESTASI ORIENTASI KEAGAMAAN - Anis Rofiah (IMTIYAZ: Jurnal Ilmu Keislaman, 2018)
The Politics of identity has been a popular political attitude phenomenon nowadays. The negative effect of this attitude begins to affect harmonious life between different communities in Indonesia. This article attempt to explain the phenomenon and relate it with religious orientation to see if the shifting religious values affect the political attitude of political actors. It also tries to propose Islamic education as a form of solution.